Endofaune du substrat meuble marin de la Côte de Mostaganem - Ahmed, BOUNOUAR (My University, 2019)
The study was undertaken on 19 samples taken between 5 and 51 m depth in the West Coast of Mostaganem. This work aimed to determinate the biodiversity of the fauna living within the sediment, the type of sediment, and its content in particulate organic matter. The sampling was carried out from a small boat using a "Van Veen" grab. All the samples from Stidia and Salamandre presented common species, such those belonging to the Gastropods group (Turritella communis), those forming part of the Annelids group (Sthenelais boa), and the group of Crustaceans (Upogebia pusilla). The species identified showed a dominance of Polychaetes and Bivalves (alive). According to the results of the Shannon and Equability Index, 15 out of 19 samples indicated that the sampled habitats were out of balance. Three stations in Stidia and two in Salamandre have a certain balance in terms of biodiversity. Probably, human activities (industrial and domestic waste, port and development, etc.) have contributed to the deterioration of the quality of coastal waters and therefore, that of the sediment. The type of sediment also played a determining role for the quality of the habitat, especially regarding the ability of oxygen to penetrate the substrate. The study showed that coarse and medium sand samples contained less than 5% organic matter; probably, this type of sediment is better oxygenated. The organic matter was more concentrated (5 - <40%) in sediments composed by fine “muddy like” particles (fine sand and silts); in such a substrate, the oxygenation was probably insufficient. The sieve analysis showed that the sediment of Stidia and Salamandre presented a good range. The dominant fractions in all the samples were 0.1 mm (fine sediment) and 0.2 mm (medium sediment); fractions <0.05mm, 0.05, 0.08, 1 and 2 mm were present only in the minority of the samples.